Case Report: Novel Compound-Heterozygous Variants of SKIV2L Gene that Cause Trichohepatoenteric Syndrome 2 - Zhang, Qiao; Qian, Xia; Zhou, Jianli; Han, Lin; Zhou, Shaoming; Wang, Zhaoxia (Frontiers in Genetics, 2021)
Background: Trichohepatoenteric syndrome (THES) is a rare disease that mainly causes intractable diarrhea. It is classified into THES1 and THES2, which are associated with the tetratricopeptide repeat domain 37 (TTC37) gene and Ski2-like RNA helicase (SKIV2L) gene, respectively. THES is not very prevalent in China or worldwide, but new cases have increasingly been reported. Methods and Results: Here, we report the clinical and genetic information of a 1.5-month-old girl who was admitted to our hospital due to diarrhea and failure to thrive. Whole-exome sequencing (WES) revealed novel compound-heterozygous variants of the SKIV2L gene, c.3602_3609delAGCGCCTG (p.Q1201Rfs*2), and c.1990A > G (p.T664A) as the causative factors, which were confirmed via Sanger sequencing. Upon continuous feeding with an amino-acid formula through a gastric tube and parenteral nutrition, the patient resumed thriving and her stool frequency decreased. Conclusion: We report a girl carrying novel variants of the SKIV2L gene that cause THES2, thereby providing valuable information on the diagnosis of THES2 and expanding the spectrum of disease-causing SKIV2L mutations.